Microporous triptycene-based affinity materials on quartz crystal microbalances for tracing of illicit compounds - Prantl, Ephraim Adam Isaac; Kohl, Bernd; Ryvlin, Dimitrij; Biegger, Philipp; Wadepohl, Hubert; Rominger, Frank; Bunz, Uwe H. F.; Mastalerz, Michael; Waldvogel, Siegfried R. (ChemPlusChem, 2019)
Triptycene-based organic molecules of intrinsic microporosity (OMIMs) with extended functionalized π-surfaces are excellent materials for gas sorption and separation. In this study, the affinities of triptycene-based OMIM affinity materials on 195 MHz high-fundamental-frequency quartz crystal microbalances (HFF-QCMs) for hazardous and illicit compounds such as piperonal and (-)-norephedrine were determined. Both new and existing porous triptycene-based affinity materials were investigated, resulting in very high sensitivities and selectivities that could be applied for sensing purposes. Remarkable results were found for safrole - a starting material for illicit compounds such as ecstasy. A systematic approach highlights the effects of different size of π-surfaces of these affinity materials, allowing a classification of the properties that might be optimal for the design of future OMIM-based affinity materials.
Gesehen am 05.03.2020